The current occurrence, habitat and historical change in the distribution range of an endemic tiger beetle species Cicindela (Ifasina) willeyi Horn (Coleoptera: Cicindelidae) of Sri Lanka - Dangalle, Chandima; Pallewatta, Nirmalie; Vogler, Alfried (My University, 2011)
The current occurrence, habitat and historical change in distributional range are studied for an endemic tiger beetle species, Cicindela (Ifasina) willeyi Horn of Sri Lanka. At present, the species is only recorded from Maha Oya (Dehi Owita) and Handapangoda, and is absent from the locations where it previously occurred. The current habitat of the species is explained using abiotic environmental factors of the climate and soil recorded using standard methods. Morphology of the species is described by studying specimens using identification keys for the genus and comparing with specimens available at the National Museum of Colombo, Sri Lanka. The DNA barcode of the species is elucidated using the mitochondrial CO1 gene sequence of eight specimens of Cicindela (Ifasina) willeyi. The study suggests that Maha Oya (Dehi Owita) and Handapangoda are suitable habitats. However, its presence in only two locations and its absence from locations where it previously occurred highlights the need for conserving the natural habitats at Maha Oya (Dehi Owita) and Handapangoda, and the necessity of further studies of this kind.